Seasonal dynamics and exports of elements from a first‐order stream to a large inland lake in Michigan. Issue 10 (18th March 2019) - Hofmeister, Kathryn L.; Nave, Lucas E.; Drevnick, Paul; Veverica, Timothy; Knudstrup, Renee; Heckman, Katherine A.; Riha, Susan J.; Schneider, Rebecca L.; Walter, M. Todd
Abstract: Headwater streams are critical components of drainage systems, directly connecting terrestrial and downstream aquatic ecosystems. The amount of water in a stream can alter hydrologic connectivity between the stream and surrounding landscape and is ultimately an important driver of what constituents headwater streams transport. There is a shortage of studies that explore concentration–discharge ( C‐Q ) relationships in headwater systems, especially forested watersheds, where the hydrological and ecological processes that control the processing and export of solutes can be directly investigated. We sought to identify the temporal dynamics and spatial patterns of stream chemistry at three points along a forested headwater stream in Northern Michigan and utilize C‐Q relationships to explore transport dynamics and potential sources of solutes in the stream. Along the stream, surface flow was seasonal in the main stem, and perennial flow was spatially discontinuous for all but the lowest reaches. Spring snowmelt was the dominant hydrological event in the year with peak flows an order of magnitude larger at the mouth and upper reaches than annual mean discharge. All three C‐Q shapes (positive, negative, and flat) were observed at all locations along the stream, with a higher proportion of the analytes showing significant relationships at the mouth than at the mid or upper flumes. At the mouth, positive (flushing) C‐Q shapes were observed for dissolved organic carbon and total suspended solids, whereas negative (dilution) C‐Q shapes were observed for most cations (Na +, Mg 2+, Ca 2+ ) and biologically cycled anions (NO3 −, PO4 3−, SO4 2− ). Most analytes displayed significant C‐Q relationships at the mouth, indicating that discharge is a significant driving factor controlling stream chemistry. However, the importance of discharge appeared to decrease moving upstream to the headwaters where more localized or temporally dynamic factors may become more important controls on stream solute patterns.